2020
DOI: 10.1103/physrevmaterials.4.054408
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer-induced interfacial ferromagnetism in La0.7Sr0.3MnO3/NdNiO3

Abstract: Charge-transfer-induced interfacial ferromagnetism and its impact on the exchange bias effect in La 0.7 Sr 0.3 MnO 3 /NdNiO 3 correlated oxide heterostructures were investigated by soft x-ray absorption and x-ray magnetic circular dichroism spectra in a temperature range from 10 to 300 K. Besides the antiferromagnetic Ni 3+ cations which are naturally part of the NdNiO 3 layer, Ni 2+ ions are formed at the interface due to a charge-transfer mechanism involving the Mn element of the adjacent layer. They exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…The interfacial ferromagnetism previously was explained as consequences of a charge transfer from FM layer to Ni sites. [ 26 , 30 ] However, our study shows that it can be induced in the NNO primarily by the stray field from the LSMO layer, which aligns the spins at Ni sites. We demonstrate that, in addition to strain and film thickness, the proximity layer emerges as an additional “knob” for manipulating existing and inducing novel physical properties, consequently ameliorating the phase diagram of RE NiO 3 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The interfacial ferromagnetism previously was explained as consequences of a charge transfer from FM layer to Ni sites. [ 26 , 30 ] However, our study shows that it can be induced in the NNO primarily by the stray field from the LSMO layer, which aligns the spins at Ni sites. We demonstrate that, in addition to strain and film thickness, the proximity layer emerges as an additional “knob” for manipulating existing and inducing novel physical properties, consequently ameliorating the phase diagram of RE NiO 3 .…”
Section: Discussionmentioning
confidence: 81%
“…Consequently, the ferromagnetism at the interface emerges by the exchange coupling between Ni2 + and Mn4 + ions. [ 26 ] Furthermore, it is also reported that interfacing the NNO layer with AF insulating (in its bulk form) NdMnO 3 layer ferromagnetic interplays between Mn and Ni ions occurs at low T. Although the charge transfer cannot be foreseen directly, the authors speculate that an epitaxial strain in NdNiO 3 /NdMnO 3 heterostructures is responsible for the different transport behavior. Dhaka et al., indeed found that a moderate compressive epitaxial strain very much alters the electronic structure and, therefore, transport properties on NNO film, primarily due to band reordering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…97,100 ICT has been also reported at the interface of nickelates with mixed-valent manganite. [101][102][103][104] Among several reports, the most notable observation is the existence of helical spin arrangements within LNO layers, containing atomic-like Ni +2 with 3d 8 electron configuration. 101,102 Wrobel et al investigated a series of La 2 CuO 4 /LaO/LaNiO 3 heterostructures to separate the dopant and doped layers from each other.…”
Section: Current Statusmentioning
confidence: 99%